Interlocus gene conversion events introduce deleterious mutations into at least 1% of human genes associated with inherited disease - Casola, Claudio; Zekonyte, Ugne; Phillips, Andrew D.; Cooper, David N.; Hahn, Matthew W. (Genome Research, 2012)
Establishing the molecular basis of DNA mutations that cause inherited disease is of fundamental importance to understanding the origin, nature, and clinical sequelae of genetic disorders in humans. The majority of disease-associated mutations constitute single-base substitutions and short deletions and/or insertions resulting from DNA replication errors and the repair of damaged bases. However, pathological mutations can also be introduced by nonreciprocal recombination events between paralogous sequences, a phenomenon known as interlocus gene conversion (IGC). IGC events have thus far been linked to pathology in more than 20 human genes. However, the large number of duplicated gene sequences in the human genome implies that many more disease-associated mutations could originate via IGC. Here, we have used a genome-wide computational approach to identify disease-associated mutations derived from IGC events. Our approach revealed hundreds of known pathological mutations that could have been caused by IGC. Further, we identified several dozen high-confidence cases of inherited disease mutations resulting from IGC in ∼1% of all genes analyzed. About half of the donor sequences associated with such mutations are functional paralogous genes, suggesting that epistatic interactions or differential expression patterns will determine the impact upon fitness of specific substitutions between duplicated genes. In addition, we identified thousands of hitherto undescribed and potentially deleterious mutations that could arise via IGC. Our findings reveal the extent of the impact of interlocus gene conversion upon the spectrum of human inherited disease.
10.1101/gr.127738.111